Analysis of innovative activity of enterprises in the Republic of Kazakhstan - Pazilov, G.A.; Ramashova, A.N.; Ramashov, N.; Kalbayeva, Nursulu (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of research article is to identify the main problems by analyzing the current state of innova tive activity of enterprises in the Republic of Kazakhstan.as well as to propose specific mechanisms and ways to devel op state support for innovative activities of domestic enterprises in the future. Methods: Theoretical methods were used at the process of the study, in particular, comparative, quantitative and systematic analysis, synthesis, expert assessment, generalization of research results. Findings: As it became known from the results of the analysis obtained during the study, in recent years there have been no significant changes in the share of innovative products produced by domestic enterprises in Gross Domes tic Product, the innovative activity of enterprises remains at a very low level. Most of the costs of innovation are fi nanced from enterprises own funds banking resources, the bulk goes to the purchase of modern machines, equipment, software and other complex products. Conclusions: For today, the state has done a lot of work to ensure the innovative development of the country and this work continues. In order to ensure innovative development on the part of the state, despite the adoption of laws, state programs and strategic documents, it becomes obvious that additional specific support measures aimed at support ing innovation activities are needed. Because the measures taken do not show successful innovative development. Therefore, according to the results of the study, it was proposed to use in parallel the mechanisms of financial, adminis trative and infrastructural influence of the state for the development of innovative activities, increasing the innovative activity of domestic enterprises.